The complete mitochondrial genome of Leptopilina syphax (Hymenoptera: Figitidae) - Zhang, Qichao (Mitochondrial DNA B Resour, 2021)
Leptopilina syphax (Hymenoptera: Figitidae) is a newly recorded species of parasitic wasp, and it attacks the larval stage of Drosophilidae, mainly the Drosophila species. Few works have been done in the basic study of L. syphax, including the data of mitochondrial genome. In this study, the complete mitochondrial genome of L. syphax (GeneBank accession number: MT649407) was sequenced using Illumina HiSeq X Ten system. The mitochondrial genome is 15,882bp long and comprises 13 protein-coding genes, 2 ribosomal RNA genes and 22 transfer RNA genes. Meanwhile, 26 genes are in majority strand, and the remaining 11 genes are in minority strand. The overall base composition is 41.7% for A, 6.0% for G, 13.6% for C, and 38.7% for T, with an A + T content of 80.4%, respectively. We also performed a phylogenetic analysis with other known mitochondrial genomes of some parasitic wasps. The results show that L. syphax is closely related to L. boulardi, which is another Drosophila parasitoid.